Case Report: Giant axillary lipoma in an infant - Ren, Haiyang; Lv, Haoqiang; Wang, Chuanjun; Liu, Hao; Liu, Xiurui; Wei, Hua; Tian, Ping (Frontiers in Pediatrics, 2024)
Lipoma is a benign mesenchymal tissue tumor, mainly composed of mature adipose cells; it is most common in adults and is rarely observed in children. The clinical data of an infant diagnosed with a giant axillary lipoma admitted to our hospital were analyzed. A 12-month-old girl presented with a large mass in the right axillary region. Imaging examination suggested a mesenchymal tissue tumor and postoperative pathology confirmed lipoma.